Reducing Fuel Subsidy or Taxing Carbon? Comparing the Two Instruments from the Economy, Environment, and Equity Perspectives for Indonesia - Yusuf, Arief Anshory; Ramayandi, Arief (Institute for Economic and Social Research, 2010)
.